Outcomes of children with cystic fibrosis screen positive, inconclusive diagnosis/CFTR related metabolic syndrome - Gunnett, Mohini A.; Baker, Elizabeth; Mims, Cathy; Self, Staci T.; Gutierrez, Hector H.; Guimbellot, Jennifer S. (Frontiers in Pediatrics, 2023)
Background. Some infants undergoing newborn screening (NBS) tests have inconclusive sweat chloride test (SCT) results that lead to the designation of Cystic Fibrosis Screen Positive, Inconclusive Diagnosis/CFTR-related metabolic syndrome (CFSPID/CRMS). Some proportion of them transition to a CF diagnosis, but no predictive markers can stratify which are at risk for this transition. We report single-center outcomes of children with CRMS. Methods. We retrospectively identified all infants born in Alabama from 2008 through 2020 referred to our CF Center with an elevated immunoreactive trypsinogen level (IRT) associated with a cystic fibrosis transmembrane conductance regulator (CFTR) mutation (IRT+/DNA+) who had at least one SCT result documented. Infants were classified per established guidelines as Carrier, CRMS, or CF based on the IRT+/DNA+ and SCT results. The electronic health record was reviewed for follow-up visits until the children received a definitive diagnosis (to carrier or CF) according to current diagnostic guidelines for CF, or through the end of the 2020 year. Results. Of the 1,346 infants with IRT+ and at least 1 CFTR mutation identified (IRT+/DNA+), 63 (4.7%) were designated as CRMS. Of these infants, 12 (19.1%) transitioned to Carrier status (CRMS-Carrier), 40 (63.5%) of them remained CRMS status (CRMS-Persistent) and 11 (17.5%) of them transitioned to a diagnosis of CF (CRMS-CF). Of the 11 children in the CRMS-CF group, 4 (36%) had an initial SCT 30-39 mmol/L, 4 (36%) had an initial SCT 40-49 mmol/L and 3 (27%) had an initial SCT 50-59 mmol/L. These children also had higher initial sweat tests and greater yearly increases in sweat chloride values than others with CRMS. We found that in comparison to children in the CRMS-P group, a greater proportion of children in the CRMS-CF group cultured bacteria like methicillin-resistant Staphylococcus aureus, Stenotrophomonas maltophilia, and Pseudomonas aeruginosa, had smaller weight-for-height percentiles and remained smaller over time despite slightly greater growth. Conclusion Infants with an inconclusive diagnosis of CF should continue to receive annual care and management given their potential risk of transition to CF. Further research is needed to assess whether certain phenotypic patterns, clinical symptoms, diagnostic tests or biomarkers could better stratify these children.